Science education reform conundrum: An analysis of teacher developed common assessments. (25th April 2021) - Pitot, Lisa N.; Balgopal, Meena
Abstract: Science education reform efforts have highlighted the need for scientifically literate citizens, who are capable of using scientific knowledge and skills for reasoning, argumentation, and decision‐making. Concurrently, recent state education policies dictate that teachers' effectiveness is measured in part by their students' performance on high stakes assessments. To study these potentially competing reform efforts, we used multiple methods to examine (a) the level of secondary science teachers scientific literacy (SL) and their perceptions of SL skills, (b) how they rank the importance of SL skills and their self reported teaching/assessment of SL skills, and (c) how well their teacher developed common science assessments aligned with SL skills. Survey responses from secondary science teachers ( n = 48) from one district revealed that their perceptions of scientific literacy were not in alignment with those of science education reform documents. Secondary science teachers ( n = 28) demonstrated that they were scientifically literate, yet the assessments ( n = 13) they developed did not align with several scientific literacy sub‐constructs. The findings from this study imply that science teachers would benefit from professional development to increase their assessment literacy and that school districts should reconsider whether teacher‐designed assessments should be tied to teachers' professional security and advancement.